1997
DOI: 10.1074/jbc.272.14.9204
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Specificity of the Hepatitis C Virus Serine Protease NS3

Abstract: The substrate specificity of a purified protein encompassing the hepatitis C virus NS3 serine protease domain was investigated by introducing systematic modifications, including non-natural amino acids, into substrate peptides derived from the NS4A/NS4B cleavage site. Kinetic parameters were determined in the absence and presence of a peptide mimicking the protease co-factor NS4A (Pep4A). Based on this study we draw the following conclusions: (i) the NS3 protease domain has an absolute requirement for a small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
122
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(125 citation statements)
references
References 39 publications
3
122
0
Order By: Relevance
“…NS3-4A is therefore thought to bind its substrate via an extensive network of weak interactions, spanning over 10 substrate residues. 20,21 These observations posed a challenge to the development of traditional competitive substrate inhibitors. A breakthrough in this arena was the unusual observation that N-terminal cleavage products (i.e., the nonprime side) bind NS3-4A and competitively block substrate recognition.…”
Section: Commentsmentioning
confidence: 99%
“…NS3-4A is therefore thought to bind its substrate via an extensive network of weak interactions, spanning over 10 substrate residues. 20,21 These observations posed a challenge to the development of traditional competitive substrate inhibitors. A breakthrough in this arena was the unusual observation that N-terminal cleavage products (i.e., the nonprime side) bind NS3-4A and competitively block substrate recognition.…”
Section: Commentsmentioning
confidence: 99%
“…Both domains can be expressed in isolation as fully active and stably folded proteins. In line with functional studies, the X-ray structure of the full-length NS3 protein showed that the protease and helicase domains are segregated and connected by a single strand (52).NS3-4Ap specificity has been defined by identification (17, 44) and mutagenesis (5,23,49,53) of the natural cleavage sites and selection of optimized cleavage sites using peptide libraries (21, 41). The NS3/NS4A junction is cleaved in cis and tolerates substitutions at all positions except P1, where a threonine residue is found in all isolates.…”
mentioning
confidence: 99%
“…S4C) resulting in a more remote positioning of the scissile bond. Similarly, the adjacent Leu-10, which binds to the subsite S1Ј, moves the peptide backbone away from the active site, although the S1Ј pocket was shown to bind larger side chains than the natural P1Ј serine (29). Additionally, Leu-10 causes dislocation of a nearby NS3-4A loop (Thr-38 -Gln-41) (Fig.…”
mentioning
confidence: 99%